The effect of pressure on the electrical conductivity of KTB rocks - Nover, Georg; Heikamp, S.; Kontny, Agnes; Duba, Al (Surveys in geophysics, 1995)
Complex electrical resistivity and permeability were measured on two gneiss samples and nine amphibolites (originally located at a depth of 4150 m to 5012 m) from the main drilling of the German deep drilling project (KTB). Measurements were performed as a function of hydrostatic pressures up to 240 MPa on core samples (30 mm in diameter and 10-20 mm high). For each measurement, two samples were used, one being parallel, and one perpendicular to the borehole axis. At low pressures and again at maximum pressure the frequency dispersion (1 kHz up to 1 MHz) of the complex resistivity was measured using a two electrode device. An unusual pressure effect was detected on some of the samples and was established to be due to the oriented deposition of good conducting phases in the foliation. Rock fabric and the orientation of ore mineralization was measured on thin sections and polished sections prepared from the same samples.
Gesehen am 24.09.2020